Rationale and design of the PREDICE project: cost-effectiveness of type 2 diabetes prevention among high-risk Spanish individuals following lifestyle intervention in real-life primary care setting - Bolíbar Bonaventura; Cos Xavier; Piñol Josep L; Barrio Francisco; Solà-Morales Oriol; Sagarra Ramon; Cabré Joan J; Costa Bernardo; Castell Conxa; Kissimova-Skarbek Katarzyna; Tuomilehto Jaakko (BMC, 2011)
Abstract Background Type 2 diabetes is an important preventable disease and a growing public health problem. Based on information provided by clinical trials, we know that Type 2 diabetes can be prevented or delayed by lifestyle intervention. In view of translating the findings of diabetes prevention research into real-life it is necessary to carry out community-based evaluations so as to learn about the feasibility and effectiveness of locally designed and implemented programmes. The aim of this project was to assess the effectiveness of an active real-life primary care strategy in high-risk individuals for developing diabetes, and then evaluate its efficiency. Methods/Design Cost-Effectiveness analysis of the DE-PLAN (Diabetes in Europe - Prevention using Lifestyle, physical Activity and Nutritional intervention) project when applied to a Mediterranean population in Catalonia (DE-PLAN-CAT). Multicenter, longitudinal cohort assessment (4 years) conducted in 18 primary health-care centres (Catalan Health Institute). Individuals without diabetes aged 45-75 years were screened using the Finnish Diabetes Risk Score - FINDRISC - questionnaire and a 2-h oral glucose tolerance test. All high risk tested individuals were invited to participate in either a usual care intervention (information on diet and cardiovascular health without individualized programme), or the intensive DE-PLAN educational program (individualized or group) periodically reinforced. Oral glucose tolerance test was repeated yearly to determine diabetes incidence. Besides measuring the accumulated incidence of diabetes, information was collected on economic impact of the interventions in both cohorts (using direct and indirect cost questionnaires) and information on utility measures (Quality Adjusted Life Years). A cost-utility and a cost-effectiveness analysis will be performed and data will be modelled to predict long-term cost-effectiveness. Discussion The project was intended to evidence that a substantial reduction in Type 2 diabetes incidence can be obtained at a reasonable cost-effectiveness ratio in real-life primary health care setting by an intensive lifestyle intervention. As far as we know, the DE-PLAN-CAT/PREDICE project represents the first assessment of long-term effectiveness and cost-effectiveness of a public healthcare strategy to prevent diabetes within a European primary care setting.